2023
DOI: 10.21203/rs.3.rs-3255941/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological and Physiological Responses of Suaeda salsa under Drought and Salt Stress

Jialei Li,
Yuwei Wang,
Jinbo Bao
et al.

Abstract: Drought and salt stress are major constraints for agricultural survival and development. Suaeda salsa is one of the hot spots plants in the study of drought- and salt-tolerant with important soil improvement and ecological restoration roles. Therefore, it is significant to understand the effects of water shortage and salt stress on physiological and biochemical properties of plants. In the study, two different horizontal gradients were set up to measure the phenotype, physiological and biochemical characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In the present study, glucose, fructose, betaine, and proline levels in leaves were increased under drought treatment, indicating that both inoculated and uninoculated walnuts actively accumulate osmolytes to resist drought. Li et al [41] also demonstrated that leaf soluble sugar, soluble protein, and proline levels in the walnut cultivars 'Liaoning 1' and 'Xiangling' increased with stress duration in an 18-day stress event. All of these indicate that 'Xiangling' has the ability to actively respond to drought stress, but its ability to adapt to drought decreases with the time of drought stress [41].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, glucose, fructose, betaine, and proline levels in leaves were increased under drought treatment, indicating that both inoculated and uninoculated walnuts actively accumulate osmolytes to resist drought. Li et al [41] also demonstrated that leaf soluble sugar, soluble protein, and proline levels in the walnut cultivars 'Liaoning 1' and 'Xiangling' increased with stress duration in an 18-day stress event. All of these indicate that 'Xiangling' has the ability to actively respond to drought stress, but its ability to adapt to drought decreases with the time of drought stress [41].…”
Section: Discussionmentioning
confidence: 98%
“…Li et al [41] also demonstrated that leaf soluble sugar, soluble protein, and proline levels in the walnut cultivars 'Liaoning 1' and 'Xiangling' increased with stress duration in an 18-day stress event. All of these indicate that 'Xiangling' has the ability to actively respond to drought stress, but its ability to adapt to drought decreases with the time of drought stress [41]. In addition, this study was conducted under potted conditions, and regular water supplementation may have an effect on Xiangling's stress response.…”
Section: Discussionmentioning
confidence: 98%